Relativistic equation-of-motion coupled-cluster investigation of the trends of single and double ionization potentials in the He and Be isoelectronic systems - Pathak, Himadri; Sahoo, B. K.; Sengupta, Turbasu; Das, B. P.; Vaval, Nayana; Pal, Sourav (Journal of Physics B-Atomic Molecular and Optical Physics, 2015)
We employ a four-component spinor relativistic equation-of-motion coupled-cluster (EOMCC) method within the single-and double-excitation approximation to calculate the single ionization potentials (IPs) and double ionization potentials (DIPs) of the He and Be isoelectronic sequences up to Ne. The obtained results are compared with the available results from the National Institute of Standards and Technology (NIST) database to test the performance of the EOMCC method. We also present intermediate results at different levels of approximations in the EOMCC framework to gain insight of the effect of electron correlation. Furthermore, we investigate the dependence of the IPs and DIPs of these ions on the ionic charge and observe that these follow parabolic trends. Similarities between the trends of IPs and DIPs in both the classes of considered systems are categorically demonstrated.
Keywords: coupled-cluster method; double ionization potentials; equation-of-motion theory

Radical attached aluminum nanoclusters: an alternative way of cluster stabilization - Sengupta, Turbasu; Pal, Sourav (Physical Chemistry Chemical Physics, 2016)
The stability and electronic structure of radical attached aluminum nanoclusters are investigated using density functional theory (DFT). A detailed investigation shows good correlation between the thermodynamic stability of radical attached clusters and the stability of the attached radical anions. All other calculated parameters like HOMO-LUMO gap and charge transfer are also found to be consistent with the observed thermodynamic stabilities of the complexes. Investigation of the electronic structure of radical attached complexes further shows the presence of jellium structures within the core similar to the ligated clusters. Comparison with available experimental and theoretical data also proves the validity of superatomic complex theory for the radical attached clusters as well. Based on the evaluated thermodynamic parameters, selected radical attached clusters are observed to be more thermodynamically stable in comparison with experimentally synthesized ligated clusters. Stabilization of small metal clusters is one of the greatest challenges in current cluster science and the present investigation confirms the fact that radical attached clusters can provide a viable alternative to ligated clusters in the future.